2001
DOI: 10.1002/jemt.1100
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide: Relation to integrity, injury, and healing of the gastric mucosa

Abstract: Nitric oxide (NO) plays a multifaceted role in mucosal integrity. The numerous functions of NO and the double-edged role played by NO in most of them provide a great complexity to the NO action. The three enzymatic sources of NO, neuronal NO-synthase (nNOS), endothelial NOS (eNOS), and inducible NOS (iNOS), have been characterised in the gastrointestinal tract. The protective properties of the NO derived from constitutive NO-synthases (eNOS and nNOS) have already been well established. Less clear is the role a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
72
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 121 publications
4
72
0
6
Order By: Relevance
“…The ability of endogenous NO to protect the mucosa is effective against a wide variety of damaging agents. Moreover, NO acts as the endogenous mediator for the gastroprotective actions of different antiulcer agents, several hormones and modulators of neural activity [14]. In the present study NOx levels increased significantly in the ME containing TGF-α treated groups (Figure 4) while the ulcer areas decreasing.…”
supporting
confidence: 49%
See 2 more Smart Citations
“…The ability of endogenous NO to protect the mucosa is effective against a wide variety of damaging agents. Moreover, NO acts as the endogenous mediator for the gastroprotective actions of different antiulcer agents, several hormones and modulators of neural activity [14]. In the present study NOx levels increased significantly in the ME containing TGF-α treated groups (Figure 4) while the ulcer areas decreasing.…”
supporting
confidence: 49%
“…Cooperation between NO and prostaglandins in gastroprotection was reported previously [13]. In particular, NO interacts with neuropeptides and prostaglandins to maintain mucosal integrity in basal conditions [14]. The release of NO in the ulcerated mucosa contributes to tissue repair as demonstrated by the fact that treatment with NOS inhibitors delays such a process [15].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Previous studies have revealed that WIRE stress-induced gastric mucosal damage involves increased gastric juice secretion, gastric peristalsis, gastrocirculation disturbances in mucosal tissues, reduced prostaglandin levels, low turnover of gastric mucosa and NO-induced changes in gastric mucus cells (23)(24)(25). Among these patterns, NO-mediated regulation is particularly important as it is associated with host defense and inflammatory responses (26) and also plays a pivotal role in gastric mucosal protection against damage induced by ethanol, stress, endotoxins and drugs (27). NOS activity is particularly high in gastric tissues (28), where NO helps maintain gastric tissue integrity (29), controls gastromucosal-derived blood flow (30) and increases gastric mucus synthesis and secretion (28).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that WIR-induced gastric mucosal lesions are associated with increased gastric acid production, accelerated gastric peristalsis, microcirculation disturbances in the gastric mucosa, decreased prostaglandin levels, low turnover of gastric mucous cells, and NO-mediated changes in the homeostatic functions of the gastric mucosa (20)(21)(22). Of these mechanisms, NO-mediated regulation is particularly important, as it is involved in host defense and inflammatory responses (23), and also plays a critical role in gastric mucosal protection against injury induced by pressure, ethanol, stress and/or endotoxins (24). NOS activity is particularly high in gastric tissue (25), where NO helps maintain the integrity of the gastric epithelium (26), regulates gastric mucosal blood flow (27), and stimulates gastric mucus secretion and synthesis (25).…”
Section: Discussionmentioning
confidence: 99%